VEGF-siRNA silencing induces apoptosis, inhibits proliferation and suppresses vasculogenic mimicry in osteosarcoma in vitro - Mei, J.; Gao, Y.; Zhang, L.; Cai, X.; Qian, Z.; Huang, H.; Huang, W. (Experimental Oncology, 2008)
Aim: To inhibit the gene expression of vascular endothelial growth factor (VEGF) with the RNA interference (RNAi) technique and explore its influence on the apoptosis, proliferation, vasculogenic mimicry of osteosarcoma in vitro. Methods: PSilencer-VEGF plasmid transfected into osteosarcoma cell line of MG63 was recombinated by gene cloning, and VEGF expression was examined by Western blotting after transfection. The biological features of transfected MG63 including proliferation, apoptosis and vasculogenic mimicry, were assessed by MTT assay, flowcytometer, annexin V-FITC/PI, light microscopy and HE staining. Results: The sequence of pSilencer-VEGF plasmid was confirmed by DNA sequencing. Sequence-specific siRNA targeting VEGF significantly decreases its expression in MG63 cells. Cell growth was inhibited and early apoptosis was induced compared with non-siRNA tansfected cells. Decreased VEGF expression was associated with reduced vasculogenic mimicry of MG63 cells. Conclusions: VEGF gene might be closely related to the apoptosis and proliferation of osteosarcoma cells, and appears to be crucial for formation of vasculogenic mimicry in osteosarcoma. Inhibition of VEGF expression by sequence-specific siRNA may become a novel approach for the treatment of VEGF-enriched neoplasma such as osteosarcoma.